(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Epiphytic bryophytes are important biodiversity elements in forest ecosystems globally. In addition, bryophytes take part in ecosystem functioning and are excellent environmental indicators. Almost half of the red-listed bryophyte distribution in Latvia is related to forest habitats. However, despite the increasing knowledge about epiphyte ecology, we are lacking information about individual rare species environmental demands. The present study aimed to evaluate the transplant disc method in rare liverwort transplantation success in aspen forest. As a result, we found that the transplant disc method can be used in epiphytic liverwort studies, but improvements are recommended in sealant selection for transplantation. Liverwort transplants were sensitive to changed substrate quality. Although transplant physiological stress during the transplantation experiment could be important. Epiphyte transplantation studies could help to test epiphyte sensitivity to global climate change in the future.